Characteristics and smoking behaviors among patients with drug-resistant tuberculosis (DR-TB) in South Africa - Phindile Zifikile Shangase; Brandon S. Shaw; Ina Shaw (BMC Public Health)
Abstract Introduction Cigarette smoking is an independent risk factor for drug-resistant tuberculosis (DR-TB), highlighting the importance of developing effective smoking cessation strategies tailored to specific contextual insights.The aim of this study was to assess the smoking behaviours, cessation attempts, and associated factors among patients with drug-resistant tuberculosis (DR-TB). Methods A cross-sectional study was conducted in three specialized DR-TB public hospitals in the KwaZulu-Natal province, South Africa. Data were collected using a structured interviewer-administered questionnaire adapted from the Global Adult Tobacco Survey. 196 participants (172 males, 24 females) with an average age of 36.13 years ± 10.27 SD were included. Results The study found 172 of the 196 participants to be male. The mean age of the participants was 36.13 years ± 10.27 SD, with 182 between the ages 21 and 50 years old. 64% had completed secondary level of education, followed by 21% who had primary schooling. 63% were unemployed. Of the participants, 95.3% smoked daily: 36.2% within five minutes of waking, 25.5% within 30 min, and 31.1% within one hour. Manufactured cigarettes were used by 84.8%, while 21.8% preferred self-rolled cigarettes. Only 64% disclosed their smoking behaviour upon hospital admission. In the past year, the following reasons were given for attempts to quit smoking, TB diagnosis (111/196), health concerns (44/196), and personal factors (20/196). Conclusion The findings underscore the urgent need for targeted smoking cessation interventions integrated into DR-TB care, emphasizing consistent counselling, improved disclosure of smoking behaviors, and enhanced education on smoking risks to support patients in quitting.